On the role of electricity storage in capacity remuneration mechanisms. (February 2021) - Fraunholz, Christoph; Keles, Dogan; Fichtner, Wolf
Abstract: In electricity markets around the world, the substantial increase of intermittent renewable electricity generation has intensified concerns about generation adequacy, ultimately driving the implementation of capacity remuneration mechanisms. Although formally technology-neutral, substantial barriers often exist in these mechanisms for non-conventional capacity such as electricity storage. In this article, we provide a rigorous theoretical discussion on design parameters and show that the concrete design of a capacity remuneration mechanism always creates a bias towards one technology or the other. In particular, we can identify the bundling of capacity auctions with call options and the definition of the storage capacity credit as essential drivers affecting the future technology mix as well as generation adequacy. In order to illustrate and confirm our theoretical findings, we apply an agent-based electricity market model and run a number of simulations. Our results show that electricity storage has a capacity value and should therefore be allowed to participate in any capacity remuneration mechanism. Moreover, we find the implementation of a capacity remuneration mechanism with call options and a strike price to increase the competitiveness of storages against conventional power plants. However, determining the amount of firm capacity an electricity storage unit can provide remains a challenging task. Highlights: Barriers exist for electricity storage to participate in some capacity mechanisms. Specification of a capacity mechanism affects technology mix and generation adequacy. Call options with a strike price increase the competitiveness of electricity storage. Low storage capacity credits create a strong bias towards conventional power plants. Capacity mechanisms should account for the capacity value of electricity storage.